Features diagnostics gifted preschoolers - Nadiia Lazarovych (Vasyl Stefanyk Precarpathian National University, 2017)
Authors of the article analyze the problem of development of mathematical speech fromthe side of P. Galperin intellectual actions formation theory. The role of first and secondsignal systems in child's learning of mathematical definitions is being validated and specialtraits learning of mathematical terms and definitions by children of early and preschool age isbeing comprehended: figure, quantity, scope, form, etc. Based on step-by-step theory ofintellectual actions, publication authors explain their own approach to provision of activemathematical speech development; by the example of integrated didactic module special traitsof comprehension by children of senior preschool age of logical operations, word terms, word'constructions are being commented; games and game exercises of logic-mathematicaldirectivity. Key words: intellectual actions formation steps, first and second signal systems,preschooler's mathematical speech , mathematical development, integrated didactic module.